Bioactive polysaccharide-based pH-sensitive polymers for cytoplasmic delivery of antigen and activation of antigen-specific immunity. (March 2017) - Yuba, Eiji; Yamaguchi, Ayaka; Yoshizaki, Yuta; Harada, Atsushi; Kono, Kenji
Abstract: For establishment of cancer immunotherapy, antigen carriers are needed which have functions not only to deliver antigen into cytosol of dendritic cells (DCs), which induces antigen-specific cellular immune responses, but also to activate DCs. We previously reported cytoplasmic delivery of antigen using liposomes modified with pH-sensitive polymers such as carboxylated poly(glycidol)s or dextran. Modification using these polymers provides stable liposomes with pH-sensitive fusogenic/membrane-disruptive ability. For this study, bioactive polysaccharide-based pH-sensitive polymers were constructed to achieve not only cytoplasmic delivery of antigen but also activation of DCs. Curdlan and mannan were used as bioactive polysaccharides because they are known to activate DCs via their respective interactions with Dectin-1 and Dectin-2. Carboxylated curdlan and mannan promoted Th1 cytokine production from DCs, indicating the activation of DCs by these polysaccharide derivatives. These polymer-modified liposomes released their contents at weakly acidic pH and delivered model antigenic proteins into cytosol of DCs. Subcutaneous administration of curdlan derivative-modified or mannan derivative-modified liposomes induced strong antigen-specific immune responses and stronger antitumor effects than those of liposomes modified with dextran derivative. Therefore, bioactive polysaccharide-modified liposomes that achieve both cytoplasmic delivery of antigen and activation of DCs are promising for cancer immunotherapy.